2022
DOI: 10.1177/15579883221084490
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Community-Based Men’s Sheds in Health Promotion for Older Men: A Mixed-Methods Systematic Review

Abstract: Men’s Sheds are a community-based health promotion concept which brings men together to engage in joint activities. Prior research reported beneficial effects on health and well-being of the participants; however, evidence is limited. The main objective of this systematic review is to provide an extensive overview of current research on the effectiveness of Men’s Sheds on self-rated health, social isolation, and well-being by applying a mixed-methods approach. In addition, this review aims to identify how to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Decrease in depression and anxiety identified in this review could, in part, be due to overcoming feelings of loneliness. 58 , 59 These findings are consistent with results identified in similar community-based programs targeting older people, (such as Men’s Sheds 60 ) and other systematic reviews of the literature exploring programs in residential aged care facilities. 61 , 62 …”
Section: Discussionsupporting
confidence: 83%
“…Decrease in depression and anxiety identified in this review could, in part, be due to overcoming feelings of loneliness. 58 , 59 These findings are consistent with results identified in similar community-based programs targeting older people, (such as Men’s Sheds 60 ) and other systematic reviews of the literature exploring programs in residential aged care facilities. 61 , 62 …”
Section: Discussionsupporting
confidence: 83%
“…Although Sheds appeal to predominantly retired men, they have demonstrated their inclusivity for men from diverse backgrounds and varying abilities, also offering opportunities for intergenerational learning [ 32 , 37 , 38 ]. Although, Sheds are not explicitly considered health interventions [ 35 ], research has demonstrated Shedders’ agency in organising health promotion activities within Sheds such as mental health and prostate cancer talks, demonstrating a willingness to engage with health and wellbeing in Sheds [ 39 , 40 ]. Based upon their inherent health promoting qualities and ready access to men who may be reticent to engage with traditional health services, Sheds represent an attractive setting in which to build structured health initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] examined similarities and differences across different types of SI&L interventions, while 21 [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ] reviews focused on a specific type. Of these, 4 [ 44 , 45 , 46 ] examined social facilitation interventions; 4 [ 47 , 48 , 49 ] focused on psychological therapy interventions; 5 [ 50 , 51 , 52 , 53 , 54 ] explored social prescribing interventions; 2 [ 55 , 56 ] investigated be-friending interventions; 2 [ 57 , 58 ] studied animal-assisted interventions; 2 [ 59 , 60 ] reviewed physical activity interventions; 1 [ 61 ] examined leisure–skill development interventions; 10 [ 62 , 63 , 64 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The majority of reviews included studies that examined the impact of SI&L interventions in the general older adult population living in the community ( Table 1 ) [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 46 , 49 , 50 , 55 , 56 , 57 , 58 , 59 , 68 , 69 ]. One focused specifically on older men [ 44 ]. Four reviews included equity-deserving groups of older adults as a primary target population.…”
Section: Resultsmentioning
confidence: 99%